Packaging Innovation for Dry Fish Lemuru Products in Perancak Village, Jembrana Regency, Bali - Ni Made Ayu Suardani Singapurwa; I Putu Candra; I Nyoman Rudianta; Ni Komang Armaeni (PT FORMOSA CENDEKIA GLOBAL, 2023)
Vacuum packaging is one way to extend the shelf life of dry food products. Dry fish lemuru is one of the regional superior products in Jembrana Regency, Bali. Processing of these fishery products has been produced and marketed by them, but not yet intensively, and they want to increase the quantity and quality. This community did not have prior knowledge in the field of business management, so they experienced obstacles in managing production and marketing. Solutions made to solve the problems faced by them were: providing appropriate technology in processing the fish products as well as storing and packaging with vacuum packaging methods including marketing, and business management. The output targets achieved were appropriate technology for traditional fishery processing; increased turnover; increased product quality and quantity.